Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Hasil Belajar IPA Peserta Didik Kelas VIII SMPN 1 Liukang Tangaya - Anna Mantovani; Sitti Saenab; Muhammad Aqil Rusli (Celebes Science Education, 2022)
This research is a pre-experimental design that aims to: 1) the high learning outcomes studentof class VII MTs Darunnaiem Pesse before using comic media. 2) the high learning outcomes student of class VII MTs Darunnaiem Pesse after using comic media. 3), imroving the learning outcomes student of class VII MTs Darunnaiem Pesse before and after using comic media, 4) high determine whether there is an effect of the application of comic media on the learning outcomes studentsof class VII MTs Darunnaiem Pesse. The data wereanalyzed using descriptive data analysis. Based on analyzed concluded: 1) the learning outcomes studentof class VII before using comic media was average 10,95 is low category, 2) the learning outcomes student of class VII after using comic media was average 18,52 is medium category, 3) the icrease learning outcomes student of class VII before and after using comic media is include in the medium category with an n-Gain value of 0,54. 4). Based on hypothesis testing using t-tes concluded tcount = 6.1 > ttable = 1.72 this means that H0 is rejected and H1 is accepted. So, it can be concluded that the application of comics media has an effect on improving the learning outcomes students of class VII MTs Darunnaiem Pesse.